The MIK2/SCOOP Signaling System Contributes to Arabidopsis Resistance Against Herbivory by Modulating Jasmonate and Indole Glucosinolate Biosynthesis - Stahl, Elia; Fernandez Martin, Angel; Glauser, Gaétan; Guillou, Marie-Charlotte; Aubourg, Sébastien; Renou, Jean-Pierre; Reymond, Philippe (Frontiers in Plant Science, 2022)
Initiation of plant immune signaling requires recognition of conserved molecular patterns from microbes and herbivores by plasma membrane-localized pattern recognition receptors. Additionally, plants produce and secrete numerous small peptide hormones, termed phytocytokines, which act as secondary danger signals to modulate immunity. In Arabidopsis, the Brassicae-specific SERINE RICH ENDOGENOUS PEPTIDE (SCOOP) family consists of 14 members that are perceived by the leucine-rich repeat receptor kinase MALE DISCOVERER 1-INTERACTING RECEPTOR LIKE KINASE 2 (MIK2). Recognition of SCOOP peptides elicits generic early signaling responses but knowledge on how and if SCOOPs modulate specific downstream immune defenses is limited. We report here that depletion of MIK2 or the single PROSCOOP12 precursor results in decreased Arabidopsis resistance against the generalist herbivore Spodoptera littoralis but not the specialist Pieris brassicae. Increased performance of S. littoralis on mik2-1 and proscoop12 is accompanied by a diminished accumulation of jasmonic acid, jasmonate-isoleucine and indolic glucosinolates. Additionally, we show transcriptional activation of the PROSCOOP gene family in response to insect herbivory. Our data therefore indicate that perception of endogenous SCOOP peptides by MIK2 modulates the jasmonate pathway and thereby contributes to enhanced defense against a generalist herbivore.